Peningkatan Motivasi Belajar Peserta Didik dengan Penerapan Konsep Culturally Responsive Teaching (CRT) pada Pembelajaran PJOK di SMA 1 Taman Sidoarjo: - Munir, Syaiful; Rufi’i; Ardiansyah, Syahrul; Baskara, Sula Dwi Pura; Aulia, Tifani Ismi; Qonitatillah, Riskiyatul; Prastiza, Twin Exa (MAN Insan Cendekia Jambi, 2025)
This study aims to increase students' learning motivation in learning Physical Education, Sports, and Health (PJOK) through the application of the Culturally Responsive Teaching (CRT) approach at the high school level. The research method used Classroom Action Research (PTK) with two cycles. The research instruments were observation, motivation questionnaire, and interview. The results showed a significant increase in learning motivation indicators after the implementation of the CRT approach. The findings suggest that CRT can be an effective strategy to increase student engagement in PJOK learning, especially considering the cultural background of the participants.